STUDIES ON THE CHOICE OF THE HYBRID, AN IMPORTANT LINK IN THE TECHNOLOGICAL MANAGEMENT OF THE CORN CROP AND ITS ECONOMIC EFFICIENCY, ACCORDING TO THE TESTS CARRIED OUT ON THE CHERNOZEM SOIL FROM CARAC - Iulia Oana ȘTEFAN; Gabriela PĂUNESCU; Ramona Aida PĂUNESCU; Aurel Liviu OLARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the period 2020-2023, on the chernozem from Caracal, numerous corn hybrids of different origins and with vegetation periods placed in almost all FAO precocity groups were tested. In 3 of the 4 years of testing, production stability was average (CV 13.4% in 2020, 15.9% in 2021 and 17.3% in 2022). Following the boxplot analysis the hybrids P0710 (Corteva) and Kashmir (KWS) stood out as positive outliers in 2021 and MAS 448 (Mass Seeds) in 2023. Although an average of 70 hybrids were tested annually, their production average was extremely close in years with favorable climatic conditions (6,654 kg/ha in 2020, 6,603 kg/ha in 2021, 6,795 kg/ha in 2023). The studies highlighted: the adaptability of a very large number of hybrids for the chernozem area in Olt County; average production stability; the rich assortment of hybrids offered by large seed companies. The economic efficiency in the case of choosing the hybrid is primarily influenced by the production obtained per hectare, by its capitalization price, but also by the price of the sown seed and the bonuses garanted by the producing company. In the last 2 years, the low prices practiced in capitalizing the production have made the option for the better hybrid which brings profit.